2017
DOI: 10.1177/1558944717743597
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Expected Costs of Carpal Tunnel Syndrome Treatment Strategies

Abstract: Although many factors must be considered when deciding upon treatment for carpal tunnel syndrome, direct payer cost is an important component, and the initial management with steroid injections minimizes these direct payer costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 26 publications
(35 reference statements)
1
22
0
6
Order By: Relevance
“…Também pode ser observado que houve diferenças em relação aos protocolos utilizados, principalmente, quanto às técnicas de fisioterapia aplicadas, em que podemos notar a descrição em comum de movimentos rotacionais na água, utilização de deslizamento para estimulação tátil e cinestésica 3,[30][31][32] ; mas, dois artigos descreveram manipulação direta dos prematuros (movimentos passivos de membros e movimentos de rotação de cinturas) 30,31 . Ainda não existe uma descrição padronizada de técnicas a serem realizadas com o prematuro em meio aquático, assim como podem ser utilizados outros dispositivos além do balde para facilitar a movimentação e deslizamento do bebê na água, sendo descrito a banheira 32 , e na prática clínica o uso de bacias com diâmetro e profundidade maiores.…”
Section: Efeitos Da Hidrocinesioterapia Ou Hidroterapiaunclassified
See 1 more Smart Citation
“…Também pode ser observado que houve diferenças em relação aos protocolos utilizados, principalmente, quanto às técnicas de fisioterapia aplicadas, em que podemos notar a descrição em comum de movimentos rotacionais na água, utilização de deslizamento para estimulação tátil e cinestésica 3,[30][31][32] ; mas, dois artigos descreveram manipulação direta dos prematuros (movimentos passivos de membros e movimentos de rotação de cinturas) 30,31 . Ainda não existe uma descrição padronizada de técnicas a serem realizadas com o prematuro em meio aquático, assim como podem ser utilizados outros dispositivos além do balde para facilitar a movimentação e deslizamento do bebê na água, sendo descrito a banheira 32 , e na prática clínica o uso de bacias com diâmetro e profundidade maiores.…”
Section: Efeitos Da Hidrocinesioterapia Ou Hidroterapiaunclassified
“…Em relação aos desfechos, todos os artigos relataram melhora de parâmetros fisiológicos ou manutenção desses parâmetros dentro da faixa de normalidade, o que nos leva a inferir que a prática da hidrocinesioterapia não interfere na estabilidade clínica de prematuros 3,[30][31][32] . É de extrema importância verificar se a conduta a ser inserida na rotina da UTIN, além de ter o efeito esperado, não representa fator adicional de dor ou de estresse, que apresentam efeitos diretos de curto prazo sobre os sinais vitais, podendo levar ao aumento de gasto energético e pior prognóstico.…”
Section: Efeitos Da Hidrocinesioterapia Ou Hidroterapiaunclassified
“…Annually, more than 500 000 carpal tunnel release procedures (CTR) are performed in the United States, with an associated cost of $2 billion dollars and additional productivity losses because of CTS. 16,17 At an integrated healthcare system that assumes responsibility for costs and quality measures by contracting with worker's compensation payers, a prospective observational study demonstrated that, despite 82% adherence to quality measures, important care recommendations were overlooked, particularly monitoring of symptoms, modifying work status, and modifying exacerbating activities. In addition, there were modest disparities in quality of care by income.…”
Section: Disparities In Cts Care and Costs Of Care Of Ctsmentioning
confidence: 99%
“…Carpal tunnel syndrome is often work‐related, particularly in jobs with high hand/wrist exposure and is a major cause of workers' compensation claims. Annually, more than 500 000 carpal tunnel release procedures (CTR) are performed in the United States, with an associated cost of $2 billion dollars and additional productivity losses because of CTS …”
Section: Introductionmentioning
confidence: 99%
“…While workplace-related injuries can occur in either hand, they are more prevalent in the dominant hand and often lead to companies paying workers’ compensation claims, along with the additional recruiting, onboarding, and training costs incurred by companies to fill temporary positions. These measures can be costly to companies as there are “500,000 carpal tunnel releases costing over $2 billion performed each year in the United States” 16 .…”
Section: Introductionmentioning
confidence: 99%